PKM PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER BAGI GURU PAUD PKBM INGIN MAJU BANTAENG - Firdaus, Firdaus; A. Karim, Sugeng; Haripuddin, Haripuddin; Imran, Andi; Zulhajji, Zulhajji (Jurusan Pendidikan Teknik Elektro, 2024)
The main problem in this activity is that PAUD PKBM teachers who want to advance in Gantarang Keke District, Bantaeng Regency are not yet fully capable of making media and using computer-based learning media. This training aims to ensure that PAUD PKBM teachers who want to advance in Gantarang Keke District, Bantaeng Regency are able to make computer-based media well and interestingly and are able to use computer-based learning media. The method that will be applied in this activity is training in making computer-based learning media for PAUD PKBM teachers who want to advance in Gantarang Keke District, Bantaeng Regency. Training activities begin with providing material to increase teachers' understanding and motivation about the importance of using media in learning. Then proceed with providing material about computer applications as learning media, the next stage is providing material on how to create computer-based learning media in the form of Microsoft Office Powerpoint. Accompanying participants to practice creating computer-based learning media and giving independent assignments to participants so they are proficient in creating computer-based learning media. The output of this training activity is that PAUD PKBM teachers who want to advance in Gantarang Keke District, Bantaeng Regency understand the benefits of using media in learning and are able to create and use computer-based learning media.